Screening for late‐onset Pompe disease in Poland. (18th June 2019) - Jastrzębska, Aleksandra; Potulska‐Chromik, Anna; Łusakowska, Anna; Jastrzębski, Miłosz; Lipowska, Marta; Kierdaszuk, Biruta; Kamińska, Anna; Kostera‐Pruszczyk, Anna
Abstract : Objectives: We aimed to screen for late‐onset Pompe disease using the dried blood spot (DBS) test in a cohort of patients with limb‐girdle muscle weakness or persistent hyperCKemia. Materials and methods: Patients with limb‐girdle muscle weakness, persistently elevated CK, rigid spine syndrome, dyspnoea, myalgia or sibling of the patient diagnosed with LOPD were included in the study. Acid α‐glucosidase (GAA) activity was measured on DBS by tandem mass spectrometry and followed by genetic testing when required. Study was conducted between June 2014 and May 2017. Results: A total of 337 patients aged 32.2 years (range 2‐80) were included in the study. Late‐onset Pompe disease was diagnosed in 10 patients (3.0% of tested cohort). All were compound heterozygotes with common c.32‐13T>G mutation on one allele and missense or frameshift mutation on the other. Two of the mutations (c.1951delG and c.397T>G) were not reported previously. Seven of the patients started enzyme replacement therapy. Conclusions: DBS test is a reliable method for screening for late‐onset Pompe disease.